11th AIAA/CEAS Aeroacoustics Conference 2005
DOI: 10.2514/6.2005-3083
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the Flow and Acoustic Effects of Jet-Pylon Interaction

Abstract: Computational simulation and prediction tools were used to understand the jet-pylon interaction effect in a set of bypass-ratio five core/fan nozzles. Results suggest that the pylon acts as a large scale mixing vane that perturbs the jet flow and jump starts the jet mixing process. The enhanced mixing and associated secondary flows from the pylon result in a net increase of noise in the first 10 diameters of the jet's development, but there is a sustained reduction in noise from that point downstream. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…NASA and industry had already developed considerable experience that gave NASA the confidence that this key assumption could be realized. This understanding had been developed through a series of extensive experimental and computational studies beginning in 2002 through 2005 on the fundamental effects of jet noise reduction and jet noise source re-distribution with chevron and pylon effects [3][4][5][6][7][8][9][10][11] . Building on this information by 2009, ERA had already developed a technical path for an HWB concept to reach the noise goal.…”
Section: Introductionmentioning
confidence: 99%
“…NASA and industry had already developed considerable experience that gave NASA the confidence that this key assumption could be realized. This understanding had been developed through a series of extensive experimental and computational studies beginning in 2002 through 2005 on the fundamental effects of jet noise reduction and jet noise source re-distribution with chevron and pylon effects [3][4][5][6][7][8][9][10][11] . Building on this information by 2009, ERA had already developed a technical path for an HWB concept to reach the noise goal.…”
Section: Introductionmentioning
confidence: 99%
“…8 In this study, Jet3D is utilized to produce noise source maps which are correlated to the local flow features. This approach was recently successfully applied to separate flow nozzles with an isolated pylon by Hunter et al 9 The computational domain extends six core diameters upstream from the fan exit, 30 downstream and eight radially. Transitions from boundary to shear layer grids are smoothed to aid convergence.…”
Section: Methodsmentioning
confidence: 99%
“…5,6,9,19 The additional resolution is aimed at better resolving the complex flow initiated by both fan and core chevrons. All surfaces are gridded and run as viscous with the exception of the very small tip region of the plug and the very thin nozzle trailing edges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAA technology options were selected based on prior PAA research of interest for conventional configurations, specifically the acoustic effect of the engine pylon [6][7][8][9][10][11] and unique chevron nozzles that were designed to interact favorably with the effect of the pylon [12][13][14] . In a study by Nesbitt et al 15 it was reported that chevrons also impact jet noise source locations and their significance in the context of far-field extrapolation.…”
mentioning
confidence: 99%